Influence of Online Transportation on Mandatory and Maintenance Activities in Banda Aceh - Ferdiansyah Novriza; Roni Agusmaniza; Ary Firnanda; Santi Septiana Zarita; Cut Liliiza Yusra (Malikussaleh University, Aceh, Indonesia, 2025)
Online transportation has experienced significant growth and has become a vital element in the daily activities in Banda Aceh. Services such as Maxim, Grab, Kururio, Mr. Delivery, Sidoom, and Umma offer convenient access to transportation, goods delivery, and food services, illustrating the growing integration of digital technology into daily urban mobility and lifestyle patterns. In the context of fast-paced urban life, these platforms significantly influence the mobility patterns of the community, both in mandatory activities (such as working and studying) and maintenance activities (such as shopping, picking up children from school, and others). This study highlights the significance of examining how online transportation influences community life. It aims to assess its social, economic, and environmental impacts, identify key determinants of user preferences, and evaluate its overall contribution to improving quality of life within the evolving dynamics of urban mobility. This study employed a mixed-methods approach by integrating quantitative and qualitative techniques, with surveys serving as the primary instrument for data collection. The results indicate that the use of online transportation is influenced by factors such as income, travel time, age, gender, and household size. In terms of service preferences, Food and goods delivery dominates usage (42.9%), followed by motorcycle ride-hailing (38.1%) and cars (19%). These findings underscore the increasing significance of online transportation services in meeting daily needs and enhancing urban mobility, particularly in the areas of goods and food delivery. The results also indicate that public perceptions of the environmental impacts of online transportation remain balanced. While respondents value the improved accessibility and convenience offered by online transit, they are aware of its negative externalities, particularly its role in exacerbating traffic congestion and air pollution.